Business Model for Small-Scale Artisan Tea Family Business - Budiyoko, Budiyoko; Prayoga, Adistiar; Rusdah, Rusdah; Mehmet Sıtkı ā°lkay; Abdulhakim Madiyoh; Satriana, Eka Dewi; Afrianto, Whisnu Febry (Universitas Airlangga, 2024)
Background: Tea stands as one of Indonesia's primary plantation commodities. The demand for tea in the domestic market is currently experiencing positive growth, reflecting shifts in consumer lifestyles and an increased interest in health products. Among the varieties of processed tea available, artisan tea stands out for its superior quality and distinctive characteristics. CV BMB, a family-owned small-scale enterprise, specializes in the development of various artisan tea products. This startup has received support from the startup incubation program provided by the Start Up-Business Development and Incubation Agency of Universitas Airlangga and the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia. Given its niche market and unique business management approach based on familial relationships, this company presents an intriguing case for analyzing its business model. Objective: This research aims to analyze the business model and competitive strategies of CV BMB, to enable it to compete effectively and sustain growth in a competitive market. Method: This research was conducted using a phenomenological approach. The analysis of CV BMB's artisan tea business model was carried out using the business model canvas. Subsequently, Porter's Five Forces analysis was conducted to obtain suitable competitive strategies for small-scale family businesses producing artisan tea. Results: Porter's Five Forces analysis successfully identified competitive elements within the artisan tea market. Additionally, nine elements in the business canvas model have been identified, contributing to the competitive strategy and development of CV BMB as a small-scale family business producing artisan tea. Three alternative strategies for BMB's business development have been outlined: market expansion, product innovation and development, and management enhancement. Conclusion: The uniqueness of BMB's artisanal tea products, and the market niche that is still open, is an opportunity for future development. As a family business company, the strategy implementation of business model analysis is expected to drive BMB's positive growth. Keywords: artisan tea; family business; business model canvas.